Analisis Respons Masyarakat terhadap Rencana Pembangunan atau Perluasan TPA di Kabupaten Madiun - Sirojudin Alfahmi; Endang Siti Rahayu; Rahning Utomowati; Dewi Handayani; Candra Purnawan (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2026)
A significant population growth rate of 1.2% per year during the 2020–2023 period has contributed to an increase in waste production in the Madiun Regency. With an average waste production of 0.7 kg per person per day, the burden of waste management in Madiun Regency continues to grow. The Kaliabu landfill is one of the main waste management facilities in Madiun Regency. This landfill accommodates more than 70% of the district's daily waste volume. With increasingly limited land, the Kaliabu landfill is expected to reach full capacity in the next 3–5 years.  This could trigger environmental problems, such as soil, water, and air pollution, and potentially disrupt the health of the surrounding community. This study aims to review the socioeconomic characteristics of the community around the planned landfill site, such as livelihoods, education levels, income, and perceptions of the landfill's existence. This study is important to understand the local community's response to the landfill's construction. The results of the study show that there are different and diverse reactions among the community, with some supporting and others opposing the landfill. The results of the study on the response of the community around the landfill show that 75% agree with the expansion or relocation of the landfill, while 25% disagree with the expansion or relocation of the landfill.